The wtf4 meiotic driver utilizes controlled protein aggregation to generate selective cell death - Nuckolls, Nicole L; Mok, Anthony C; Lange, Jeffrey J; Yi, Kexi; Kandola, Tejbir S; Hunn, Andrew M; McCroskey, Scott; Snyder, Julia L; Bravo Núñez, María Angélica; McClain, Melainia; McKinney, Sean A; Wood, Christopher; et al. (eLife, 2020)
Meiotic drivers are parasitic loci that force their own transmission into greater than half of the offspring of a heterozygote. Many drivers have been identified, but their molecular mechanisms are largely unknown. The wtf4 gene is a meiotic driver in Schizosaccharomyces pombe that uses a poison-antidote mechanism to selectively kill meiotic products (spores) that do not inherit wtf4. Here, we show that the Wtf4 proteins can function outside of gametogenesis and in a distantly related species, Saccharomyces cerevisiae. The Wtf4poison protein forms dispersed, toxic aggregates. The Wtf4antidote can co-assemble with the Wtf4poison and promote its trafficking to vacuoles. We show that neutralization of the Wtf4poison requires both co-assembly with the Wtf4antidote and aggregate trafficking, as mutations that disrupt either of these processes result in cell death in the presence of the Wtf4 proteins. This work reveals that wtf parasites can exploit protein aggregate management pathways to selectively destroy spores.
Keywords: meiosis; Meiotic drive; protein aggregation; wtf; proteostasis; autophagy